Ketika internasionale bergema lagi : koleksi rencana kritis - Li, Wanqian, 1942- (Kuala Lumpur, Malaysia : Diterbit dan diedar oleh Kinibooks.com, 2006)
Political, socioeconomic, and educational issues in Malaysia; columns previously published in Malaysiakini.
Includes bibliographical references.
In Malay.
Koleksi sumbangan Prof. Dr. Ding Choo Ming.
Keywords: Education and state -- Malaysia -- 21st century; Malaysia -- History -- 21st century; Malaysia -- Politics and government -- 21st century